2010
DOI: 10.1111/j.1365-2265.2009.03772.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity is closely correlated with neck circumference and represents a significant indicator of insulin resistance in WHO grade III obesity

Abstract: Visceral adiposity remains a strongly significant indicator of insulin resistance in WHO grade III obesity. Neck circumference surpasses other anthropometric measurements as a powerful marker of both VAT and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
75
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 18 publications
12
75
0
3
Order By: Relevance
“…32 On the other hand, BMI predictably correlated with abdominal subcutaneous adipose tissue ASAT (p = 0.002) but not VAT nor any index of insulin resistance in a study by Yang and colleagues. 32 NC used in combination with other measurements in a three compartment model of interpretable anthropometry separates the effects of visceral adipose tissue mass, subcutaneous tissue mass and subcutaneous adipose tissue distribution on metabolic parameters under crosssectional and longitudinal conditions. 24 These observations indicate that NC as an index of upper body fat distribution can be used to identify overweight and obese patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…32 On the other hand, BMI predictably correlated with abdominal subcutaneous adipose tissue ASAT (p = 0.002) but not VAT nor any index of insulin resistance in a study by Yang and colleagues. 32 NC used in combination with other measurements in a three compartment model of interpretable anthropometry separates the effects of visceral adipose tissue mass, subcutaneous tissue mass and subcutaneous adipose tissue distribution on metabolic parameters under crosssectional and longitudinal conditions. 24 These observations indicate that NC as an index of upper body fat distribution can be used to identify overweight and obese patients.…”
Section: Discussionmentioning
confidence: 91%
“…25 WC is therefore widely used as an indirect measure of visceral adipose tissue (VAT); while it is a well-validated anthropometric technique, [5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][28][29][30][31][32][33][34] there is high measurement variability which rises with increasing BMI. 32 On the other hand, BMI predictably correlated with abdominal subcutaneous adipose tissue ASAT (p = 0.002) but not VAT nor any index of insulin resistance in a study by Yang and colleagues. 32 NC used in combination with other measurements in a three compartment model of interpretable anthropometry separates the effects of visceral adipose tissue mass, subcutaneous tissue mass and subcutaneous adipose tissue distribution on metabolic parameters under crosssectional and longitudinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies indicated that NC is an index of upper body fat distribution that can be used to identify overweight and obese patients [3][4][5][6][7]. In the last decade, a few studies have suggested that NC surpasses other antropometric measurements as a powerful marker of both visceral adipose tissue and IR [11,[17][18][19]. It's reported that, NC lower than 34 cm in females and 37 cm in males indicates healthy body weight.…”
Section: Resultsmentioning
confidence: 99%
“…20 Finally, several recent studies in the able bodied identified a strong correlation between NC and visceral adipose tissue, as well as a correlation with CVD risk above and beyond the risk related to visceral fat. [25][26][27][28] Whether NC is also a predictor for obesity or other adverse cardiovascular risk factors in individuals with SCI is unknown.…”
mentioning
confidence: 99%